Osteosíntesis Tibial En Un Hurón (Mustela Putorius Furo): Reporte De Caso De Una Clínica Veterinaria En La Ciudad De Bogotá (2023)
Animal Health Tetrapoda Pets is a veterinary clinic for exotic pets and conventional located in the city of Bogotá, founded by professionals graduated from the National university of Colombia. The institution was born with the purpose of covering the growing Demand for specialized care for pets whose unconventional nature requires differential management, all this without neglecting conventional pets, which They occupy an important place in the daily practice of the clinic.